ENHANCING THE POTENTIAL OF CREATIVE INDUSTRIES ON TOURISM VILLAGES THROUGH PENTAHELIX SYNERGY - Royani, Ida (Lembaga Riset dan Pengembangan Sumatera Utara, 2025)
This research aims to analyze the Pentahelix model strategy on increasing the potential of creative industries in Paloh Naga Agrotourism. The Pentahelix model involves five main elements which work together to develop the community-based tourism destinations. This research uses a descriptive approach to describe tourism development through the Pentahelix model systematically and accurately. This research results show there is a challenge in the form of a decrease in the number of visitors after harvest which has an impact on local community income, because tourism activities are very dependent on the beauty of newly planted rice fields. But, during the pre-harvest period, tourist attraction and community income are higher. Based on these findings, the results of interviews using the Pentahelix strategy produced several strategies to overcome these challenges, including digital promotional assistance through the use of social and electronic media, providing breakfast and lunch culinary that combine traditional food and contemporary food, traditional arts performances, increasing the completeness of facilities and infrastructure, intensive promotions involving influencers. Implementation of this strategy can increase the number of tourist visits in the post-harvest period and have a positive impact on increasing people's income, even though Paloh Naga Agrotourism is in the post-harvest period